Prevalent detection of multiclass environmental chemicals in paired CSF and plasma samples and their potential associations with postpartum depressive symptoms in pregnant women - Bushra Amreen; Corina Lesseur; Ravikumar Jagani; Hiraj Patel; Daniel Katz; Joshua Hamburger; Noel Strong; Leah Habersham; Anna-Sophie Rommel; Lotje D. de Witte; Chris Gennings; M Mercedes Perez-Rodriguez; et al. (Environmental Research, 2026)

High-dimensional mediation analysis to elucidate the role of metabolites in the association between PFAS exposure and reduced SARS-CoV-2 IgG in pregnancy - Haibin Guan; Jia Chen; Kirtan Kaur; Bushra Amreen; Corina Lesseur; Georgia Dolios; Syam S. Andra; Srinivasan Narasimhan; Divya Pulivarthi; Vishal Midya; Lotje D. De Witte; Veerle Bergink; et al. (Science of The Total Environment, 2025)

Towards an assessment of psychosocial work factors in a multi-level mental health intervention in the workplace: results from the MENTUPP pilot-study - Fotini Tsantila; Reiner Rugulies; Evelien Coppens; Hans De Witte; Ella Arensman; Abdulla Kahar; Arlinda Cerga-Pashoja; Paul Corcoran; Lars De Winter; Birgit Greiner; Eve Griffin; Bridget Hogg; et al. (International Archives of Occupational and Environmental Health, 2024)

Characterization of HIV variants from paired Cerebrospinal fluid and Plasma samples in primary microglia and CD4+ T-cells - Stephanie B. H. Gumbs; Arjen J. Stam; Tania Mudrikova; Pauline J. Schipper; Andy I. M. Hoepelman; Petra M. van Ham; Anne L. Borst; LMarije Hofstra; Lavina Gharu; Stephanie van Wyk; Eduan Wilkinson; Lot D. de Witte; et al. (Journal of NeuroVirology, 2024)
Despite antiretroviral therapy (ART), HIV persistence in the central nervous system (CNS) continues to cause a range of cognitive impairments in people living with HIV (PLWH). Upon disease progression, transmigrating CCR5-using T-cell tropic viruses are hypothesized to evolve into macrophage-tropic viruses in the CNS that can efficiently infect low CD4-expressing cells, such as microglia. We examined HIV-1 RNA concentration, co-receptor usage, and CSF compartmentalization in paired CSF and blood samples from 19 adults not on treatment. Full-length envelope CSF- and plasma-derived reporter viruses were generated from 3 subjects and phenotypically characterized in human primary CD4 + T-cells and primary microglia. Median HIV RNA levels were higher in plasma than in CSF (5.01 vs. 4.12 log10 cp/mL; p = 0.004), and coreceptor usage was mostly concordant for CCR5 across the paired samples (n = 17). Genetically compartmentalized CSF viral populations were detected in 2 subjects, one with and one without neurological symptoms. All viral clones could replicate in T-cells (R5 T cell-tropic). In addition, 3 CSF and 1 plasma patient-derived viral clones also had the capacity to replicate in microglia/macrophages and, therefore have an intermediate macrophage tropic phenotype. Overall, with this study, we demonstrate that in a subset of PLWH, plasma-derived viruses undergo genetic and phenotypic evolution within the CNS, indicating viral infection and replication in CNS cells. It remains to be studied whether the intermediate macrophage-tropic phenotype observed in primary microglia represents a midpoint in the evolution towards a macrophage-tropic phenotype that can efficiently replicate in microglial cells and propagate viral infection in the CNS.

Acoustic signatures of single disrupting FSP droplets in a heated oxygen atmosphere - Arne Witte; Stephen D. Tse; Lutz Mädler (Journal of Aerosol Science, 2024)

Correction: Outcome assessment of a complex mental health intervention in the workplace. Results from the MENTUPP pilot study - Fotini Tsantila; Evelien Coppens; Hans De Witte; Ella Arensman; Benedikt Amann; Arlinda Cerga-Pashoja; Paul Corcoran; Johanna Creswell-Smith; Grace Cully; Monika Ditta Toth; Birgit Greiner; Eve Griffin; et al. (International Archives of Occupational and Environmental Health, 2023)

Outcome assessment of a complex mental health intervention in the workplace. Results from the MENTUPP pilot study - Fotini Tsantila; Evelien Coppens; Hans De Witte; Ella Arensman; Benedikt Amann; Arlinda Cerga-Pashoja; Paul Corcoran; Johanna Creswell-Smith; Grace Cully; Monika Ditta Toth; Birgit Greiner; Eve Griffin; et al. (International Archives of Occupational and Environmental Health, 2023)
Objective Multicomponent interventions are recommendable to achieve the greatest mental health benefits, but are difficult to evaluate due to their complexity. Defining long-term outcomes, arising from a Theory of Change (ToC) and testing them in a pilot phase, is a useful approach to plan a comprehensive and meaningful evaluation later on. This article reports on the pilot results of an outcome evaluation of a complex mental health intervention and examines whether appropriate evaluation measures and indicators have been selected ahead of a clustered randomised control trial (cRCT). Methods The MENTUPP pilot is an evidence-based intervention for Small and Medium Enterprises (SMEs) active in three work sectors and nine countries. Based on our ToC, we selected the MENTUPP long-term outcomes, which are reported in this article, are measured with seven validated scales assessing mental wellbeing, burnout, depression, anxiety, stigma towards depression and anxiety, absenteeism and presenteeism. The pilot MENTUPP intervention assessment took place at baseline and at 6 months follow-up. Results In total, 25 SMEs were recruited in the MENTUPP pilot and 346 participants completed the validated scales at baseline and 96 at follow-up. Three long-term outcomes significantly improved at follow-up ( p < 0.05): mental wellbeing, symptoms of anxiety, and personal stigmatising attitudes towards depression and anxiety. Conclusions The results of this outcome evaluation suggest that MENTUPP has the potential to strengthen employees’ wellbeing and decrease anxiety symptoms and stigmatising attitudes. Additionally, this study demonstrates the utility of conducting pilot workplace interventions to assess whether appropriate measures and indicators have been selected. Based on the results, the intervention and the evaluation strategy have been optimised.

Cross-sectional associations of maternal PFAS exposure on SARS-CoV-2 IgG antibody levels during pregnancy - Kirtan Kaur; Corina Lesseur; Lixian Chen; Syam S. Andra; Srinivasan Narasimhan; Divya Pulivarthi; Vishal Midya; Yula Ma; Erona Ibroci; Frederieke Gigase; Molly Lieber; Whitney Lieb; et al. (Environmental Research, 2023)

Human microglial models to study HIV infection and neuropathogenesis: a literature overview and comparative analyses - Stephanie B. H. Gumbs; Raphael Kübler; Lavina Gharu; Pauline J. Schipper; Anne L. Borst; Gijsje J. L. J. Snijders; Paul R. Ormel; Amber Berdenis van Berlekom; Annemarie M. J. Wensing; Lot D. de Witte; Monique Nijhuis (Journal of NeuroVirology, 2022)
HIV persistence in the CNS despite antiretroviral therapy may cause neurological disorders and poses a critical challenge for HIV cure. Understanding the pathobiology of HIV-infected microglia, the main viral CNS reservoir, is imperative. Here, we provide a comprehensive comparison of human microglial culture models: cultured primary microglia (pMG), microglial cell lines, monocyte-derived microglia (MDMi), stem cell–derived microglia (iPSC-MG), and microglia grown in 3D cerebral organoids (oMG) as potential model systems to advance HIV research on microglia. Functional characterization revealed phagocytic capabilities and responsiveness to LPS across all models. Microglial transcriptome profiles of uncultured pMG showed the highest similarity to cultured pMG and oMG, followed by iPSC-MG and then MDMi. Direct comparison of HIV infection showed a striking difference, with high levels of viral replication in cultured pMG and MDMi and relatively low levels in oMG resembling HIV infection observed in post-mortem biopsies, while the SV40 and HMC3 cell lines did not support HIV infection. Altogether, based on transcriptional similarities to uncultured pMG and susceptibility to HIV infection, MDMi may serve as a first screening tool, whereas oMG, cultured pMG, and iPSC-MG provide more representative microglial culture models for HIV research. The use of current human microglial cell lines (SV40, HMC3) is not recommended.

Association Between Systemic Inflammation, Carotid Arteriosclerosis, and Autonomic Dysfunction - Sven Rupprecht; S. Finn; D. Hoyer; A. Guenther; O. W. Witte; T. Schultze; M. Schwab (Translational Stroke Research, 2020)

Interdisciplinary science to support North Sea marine management: lessons learned and future demands - S. Degraer; V. Van Lancker; T. A. G. P. Van Dijk; S. N. R. Birchenough; B. De Witte; M. Elliott; S. Le Bot; H. Reiss; V. Stelzenmüller; S. Van Gaever; E. Balian; D. Cox; et al. (Hydrobiologia, 2019)

Tributyltin: A Bottom–Up Regulator of the Crangon crangon Population? - Koen F. V. Parmentier; Yves Verhaegen; Bavo P. De Witte; Stefan Hoffman; Daan H. R. Delbare; Patrick M. Roose; Ketil D. E. Hylland; Thierry Burgeot; Guy J. Smagghe; Kris Cooreman (Frontiers in Marine Science, 2019)

SKIM, a Candidate Satellite Mission Exploring Global Ocean Currents and Waves - Fabrice Ardhuin; Peter Brandt; Lucile Gaultier; Craig Donlon; Alessandro Battaglia; François Boy; Tania Casal; Bertrand Chapron; Fabrice Collard; Sophie Cravatte; Jean-Marc Delouis; Erik De Witte; et al. (Frontiers in Marine Science, 2019)

Effects of Superdispersant-25 on the sorption dynamics of naphthalene and phenanthrene in marine sediments - Luis J. Perez Calderon; Lloyd D. Potts; Alejandro Gallego; James A. Anderson; Ursula Witte (Journal of Soils and Sediments, 2019)

Advective pore-water transport of hydrocarbons in North East Scotland coastal sands - Luis J. Perez Calderon; Kathrin Vossen; Lloyd D. Potts; Alejandro Gallego; James A. Anderson; Ursula Witte (Environmental Science and Pollution Research, 2018)

Bacterial Community Response in Deep Faroe-Shetland Channel Sediments Following Hydrocarbon Entrainment With and Without Dispersant Addition - Luis J. Perez Calderon; Lloyd D. Potts; Evangelia Gontikaki; Cécile Gubry-Rangin; Thomas Cornulier; Alejandro Gallego; James A. Anderson; Ursula Witte (Frontiers in Marine Science, 2018)

Drivers of interannual variability in virioplankton abundance at the coastal western A ntarctic peninsula and the potential effects of climate change - Claire Evans; Joost Brandsma; David W. Pond; Hugh J. Venables; Michael P. Meredith; Harry J. Witte; Sharon Stammerjohn; William H. Wilson; Andrew Clarke; Corina P. D. Brussaard (Environmental Microbiology, 2017)
Summary An 8‐year time‐series in the Western Antarctic Peninsula (WAP) with an approximately weekly sampling frequency was used to elucidate changes in virioplankton abundance and their drivers in this climatically sensitive region. Virioplankton abundances at the coastal WAP show a pronounced seasonal cycle with interannual variability in the timing and magnitude of the summer maxima. Bacterioplankton abundance is the most influential driving factor of the virioplankton, and exhibit closely coupled dynamics. Sea ice cover and duration predetermine levels of phytoplankton stock and thus, influence virioplankton by dictating the substrates available to the bacterioplankton. However, variations in the composition of the phytoplankton community and particularly the prominence of Diatoms inferred from silicate drawdown, drive interannual differences in the magnitude of the virioplankton bloom; likely again mediated through changes in the bacterioplankton. Their findings suggest that future warming within the WAP will cause changes in sea ice that will influence viruses and their microbial hosts through changes in the timing, magnitude and composition of the phytoplankton bloom. Thus, the flow of matter and energy through the viral shunt may be decreased with consequences for the Antarctic food web and element cycling.

Climatic variability in combination with eutrophication drives adaptive responses in the gills of Lake Victoria cichlids - Jacco C. van Rijssel; Robert E. Hecky; Mary A. Kishe-Machumu; Saskia E. Meijer; Johan Pols; Kaj M. van Tienderen; Jan D. Ververs; Jan H. Wanink; Frans Witte (Oecologia, 2016)

Capsaicin induces apoptosis in human small cell lung cancer via the TRPV6 receptor and the calpain pathway - Jamie K. Lau; Kathleen C. Brown; Aaron M. Dom; Theodore R. Witte; Brent A. Thornhill; Clayton M. Crabtree; Haley E. Perry; J. Michael Brown; John G. Ball; Rebecca G. Creel; C. Luke Damron; William D. Rollyson; et al. (Apoptosis, 2014)

Consensus Paper: Language and the Cerebellum: an Ongoing Enigma - Peter Mariën; Herman Ackermann; Michael Adamaszek; Caroline H. S. Barwood; Alan Beaton; John Desmond; Elke De Witte; Angela J. Fawcett; Ingo Hertrich; Michael Küper; Maria Leggio; Cherie Marvel; et al. (The Cerebellum, 2013)

Spatial distribution of intact polar lipids in North Sea surface waters: Relationship with environmental conditions and microbial community composition - Joost Brandsma; Ellen C. Hopmans; Corina P. D. Brussaard; Harry J. Witte; Stefan Schouten; Jaap S. Sinninghe Damsté (Limnology and Oceanography, 2012)
We characterized and quantified the intact polar lipid (IPL) composition of the surface waters of the North Sea and investigated its relationships with environmental conditions, microbial abundances, and community composition. The total IPL pool comprised at least 600 different IPL species in seven main classes: the glycerophospholipids phosphatidylcholine (PC), phosphatidylglycerol (PG), and phosphatidylethanolamine (PE); the sulfur‐bearing glycerolipid sulfoquinovosyldiacylglycerol (SQDG); and the nitrogen‐bearing betaine lipids diacylglyceryl‐trimethylhomoserine (DGTS), diacylglyceryl‐hydroxymethyltrimethylalanine (DGTA), and diacylglyceryl‐carboxyhydroxymethylcholine (DGCC). Although no significant relationships were found between the IPL composition and environmental parameters, such as nutrient concentrations, distance‐based ordination yielded distinct clusters of IPL species, which could in turn be tentatively correlated with the predominant microbial groups. SQDGs and PGs, as well as PC species containing saturated fatty acid moieties, were related to picoeukaryote abundances and PC species with polyunsaturated fatty acid (PUFA) moieties to nanoeukaryote abundances. The PEs were likely of mixed cyanobacterial–bacterial origin, whereas DGTA and DGCC species were mainly associated with cyanobacteria. DGTSs were likely derived from either pico‐ or nanoeukaryotes, although the DGTS species with PUFAs also showed some relationship with cyanobacterial abundances. Concentrations of the algal‐derived IPLs showed strong positive correlations with chlorophyll a concentrations, indicating they may be used as biomarkers for living photosynthetic microbes. However, direct relationships between the IPLs and microbial groups were relatively weak, implying that the predominant IPLs in marine surface waters are not derived from single microbial groups and that direct inferences of microbial community compositions from IPL compositions should be considered with care.

Erratum to: MG624, an α7-nAChR antagonist, inhibits angiogenesis via the Egr-1/FGF2 pathway - Kathleen C. Brown; Jamie K. Lau; Aaron M. Dom; Theodore R. Witte; Haitao Luo; Clayton M. Crabtree; Yashoni H. Shah; Brandon S. Shiflett; Aileen J. Marcelo; Nancy A. Proper; W. Elaine Hardman; Richard D. Egleton; et al. (Angiogenesis, 2012)

MG624, an α7-nAChR antagonist, inhibits angiogenesis via the Egr-1/FGF2 pathway - Kathleen C. Brown; Jamie K. Lau; Aaron M. Dom; Theodore R. Witte; Haitao Luo; Clayton M. Crabtree; Yashoni H. Shah; Brandon S. Shiflett; Aileen J. Marcelo; Nancy A. Proper; W. Elaine Hardman; Richard D. Egleton; et al. (Angiogenesis, 2012)

Transcriptome analysis of the response to chronic constant hypoxia in zebrafish hearts - Ines J. Marques; Jelani T. D. Leito; Herman P. Spaink; Janwillem Testerink; Richard T. Jaspers; Frans Witte; Sjoerd van den Berg; Christoph P. Bagowski (Journal of Comparative Physiology B, 2008)

Viruses as mortality agents of picophytoplankton in the deep chlorophyll maximum layer during IRONAGES III - Anne-Claire Baudoux; Marcel J. W. Veldhuis; Harry J. Witte; Corina P. D. Brussaard (Limnology and Oceanography, 2007)
We report viral‐induced mortality rates of the picoeukaryotic (two size classes) and prokaryotic (cyanobacteria Prochlorococcus and Synechococcus ) phytoplankton during a cruise in the oligotrophic subtropical northeastern Atlantic (October 2002). A dilution assay, simultaneously estimating viral lysis and microzooplankton grazing, was applied around the deep chlorophyll maximum (DCM) at six stations. For the smallest picoeukaryotes (group I), viral lysis was responsible for 50‐100% of the total cell losses, with rates ranging from 0.1 to 0.8 d −1 . Viral lysis rates were positively linked to the abundance and contribution of large genome‐sized (180–225 kb) putative algal viruses. In contrast, the prokaryotic picophytoplankton did not seem to be controlled by viral lysis. For Synechococcus , microzooplankton grazing dominated, with rates between 0.1 and 0.25 d −1 (comparable to those for the eukaryotic algae). For Prochlorococcus , both viral lysis and microzooplankton grazing rates were very low (0–0.1 d −1 ). Overall, the total carbon production by the picophytoplankton community was balanced by the combined losses due to viral lysis and microzooplankton grazing. Viral lysis released 0.1‐0.3 µg of picophytoplanktonic C L −1 d −1 , which comprised 21% of the total carbon production by picophytoplankton.

A new family of histamine H3 receptor antagonists based on a natural product: discovery, SAR, and properties of the series - M. Cowart; M. Sun; C. Zhao; D. G. Witte; T. R. Miller; K. M. Krueger; K. Browman; G. B. Fox; Y. L. Bennani; T. A. Esbenshade; A. A. Hancock (Inflammation Research, 2007)

Abnormal recruitment of periendothelial cells to lymphatic capillaries in digestive organs of angiopoietin-2-deficient mice - Hiroshi Shimoda; Michael J. Bernas; Marlys H. Witte; Nicholas W. Gale; George D. Yancopoulos; Seiji Kato (Cell and Tissue Research, 2007)

Effect of comorbid symptoms of oppositional defiant disorder on responses to atomoxetine in children with ADHD: a meta-analysis of controlled clinical trial data - Joseph Biederman; Thomas J. Spencer; Jeffrey H. Newcorn; Haitao Gao; Denái R. Milton; Peter D. Feldman; Michael M. Witte (Psychopharmacology, 2007)

Fluorescent benzofuran histamine H3 receptor antagonists with sub-nanomolar potency - M. Cowart; G. A. Gfesser; K. Bhatia; R. Esser; M. Sun; T. R. Miller; K. Krueger; D. Witte; T. A. Esbenshade; A. A. Hancock (Inflammation Research, 2006)

Differences in pharmacological properties of histamine H3 receptor agonists and antagonists revealed at two human H3 receptor isoforms - T. A. Esbenshade; K. M. Krueger; B. B. Yao; D. G. Witte; B. R. Estvander; J. L. Baranowski; T. R. Miller; A. A. Hancock (Inflammation Research, 2006)

Differential CNS expression and functional activity of multiple human H3 receptor isoforms - T. A. Esbenshade; M. I. Strakhova; T. L. Carr; R. Sharma; D. G. Witte; B. B. Yao; T. R. Miller; A. A. Hancock (Inflammation Research, 2006)

Characterization of methicillin-resistant Staphylococcus aureus from Ulaanbaatar, Mongolia - D. Orth; K. Grif; L. Erdenechimeg; C. Battogtokh; T. Hosbayar; B. Strommenger; C. Cuny; G. Walder; C. Lass-Flörl; M.P. Dierich; W. Witte (European Journal of Clinical Microbiology & Infectious Diseases, 2006)

Spread of ampicillin/vancomycin-resistant Enterococcus faecium of the epidemic-virulent clonal complex-17 carrying the genes esp and hyl in German hospitals - I. Klare; C. Konstabel; S. Mueller-Bertling; G. Werner; B. Strommenger; C. Kettlitz; S. Borgmann; B. Schulte; D. Jonas; A. Serr; A. M. Fahr; U. Eigner; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

New strains of community-acquired methicillin-resistant Staphylococcus aureus with Panton–Valentine leukocidin causing an outbreak of severe soft tissue infection in a football team - M. Müller-Premru; B. Strommenger; N. Alikadic; W. Witte; A. W. Friedrich; K. Seme; N. Svent Kucina; D. Smrke; V. Spik; M. Gubina (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Use of novel, non-imidazole inverse agonist radioligands to define histamine H3 receptor pharmacology - T. A. Esbenshade; B. B. Yao; D. G. Witte; T. L. Carr; R. Sharma; J. L. Baranowski; K. M. Krueger; T. R. Miller; B. W. Surber; R. Faghih; A. A. Hancock (Inflammation Research, 2005)

Emergence of methicillin-resistant Staphylococcus aureus with Panton?Valentine leukocidin genes in central Europe - W. Witte; C. Braulke; C. Cuny; B. Strommenger; G. Werner; D. Heuck; U. Jappe; C. Wendt; H.-J. Linde; D. Harmsen (European Journal of Clinical Microbiology & Infectious Diseases, 2005)

Structure-activity relationships of A-331440: a new histamine-3 antagonist with anti-obesity properties - Y. L. Bennani; A. A. Hancock; K. M. Krueger; B. B. Yao; G. B. Fox; T. M. Miller; D. G. Witte; R. Faghih; C. H. Kang; M. Cowart; T. A. Esbenshade (Inflammation Research, 2004)

In vitro pharmacological properties of two novel non-imidazole H 3 receptor (H 3 R) antagonists - D. G. Witte; T. R. Miller; R. Faghih; B. B. Yao; T. A. Esbenshade; K. M. Krueger; T. L. Carr; C. H. Kang; A. A. Hancock; Y. L. Bennani (Inflammation Research, 2003)

Risk Factors for Nasal Carriage of Staphylococcus aureus in Infectious Disease Patients, Including Patients Infected with HIV, and Molecular Typing of Colonizing Strains - D. Sissolak; A. Geusau; G. Heinze; W. Witte; M. Rotter (European Journal of Clinical Microbiology & Infectious Diseases, 2002)

Methicillin-Resistant Staphylococcus aureus Exhibiting Genomic Fingerprints of Phage Group I Strains in a Hospital and in a Nurse's Family - C. Windmeier; C. Cuny; C. Braulke; D. Heuck; W. Witte (European Journal of Clinical Microbiology & Infectious Diseases, 1999)

Application of correlation dimension and pointwise dimension for non-linear topographical analysis of focal onset seizures - M. Feucht; U. Möller; H. Witte; F. Benninger; S. Asenbaum; D. Prayer; M. H. Friedrich (Medical & Biological Engineering & Computing, 1999)

Microsatellite Variation in Two Populations of Free-Ranging Yellow Baboons (Papio hamadryas cynocephalus) - D. St. George; S. M. Witte; T. R. Turner; M. L. Weiss; J. Phillips-Conroy; E. O. Smith; J. Rogers (International Journal of Primatology, 1998)

Gene therapy for glioblestome multiforme: in vivo tumor transduction with the herpes simplex thymidine kinase gene followed by ganciclovir - G. Stockhammer; J. Brotchi; R. Leblanc; M. Bernstein; G. Schackert; F. Weber; C. Ostertag; N. H. Mulder; H. Mellstedt; R. Seiler; Y. Yonekawa; K. Twerdy; et al. (Journal of Molecular Medicine, 1997)

Meat preparation and colorectal adenomas in a large sigmoidoscopy-based case-control study in California (United States) - Nicole M. Probst-Hensch; Rashmi Sinha; Matthew P. Longnecker; John S. Witte; Sue A. Ingles; Harold D. Frankl; Eric R. Lee; Robert W. Haile (Cancer Causes & Control, 1997)